2021
DOI: 10.1038/s41598-021-95553-y
|View full text |Cite
|
Sign up to set email alerts
|

Extended in vivo transcriptomes of two ascoviruses with different tissue tropisms reveal alternative mechanisms for enhancing virus reproduction in hemolymph

Abstract: Ascoviruses are large dsDNA viruses characterized by the extraordinary changes they induce in cellular pathogenesis and architecture whereby after nuclear lysis and extensive hypertrophy, each cell is cleaved into numerous vesicles for virion reproduction. However, the level of viral replication and transcription in vesicles compared to other host tissues remains uncertain. Therefore, we applied RNA-Sequencing to compare the temporal transcriptome of Spodoptera frugiperda ascovirus (SfAV) and Trichoplusia ni a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Interestingly, a recent study reported that the host immune cascade of melanization promoted viral replication of HvAV-3h [35]. In addition to our results presented above, a variety of evidence suggests that virions produced in circulating viral vesicles are shed into the haemolymph [10,13,15], where they can also be acquired on the ovipositor of female wasps. Phylogenetic analysis indicates that ascoviruses evolved iridoviruses [36].…”
Section: Rna-sequencing Data Validationsupporting
confidence: 76%
See 4 more Smart Citations
“…Interestingly, a recent study reported that the host immune cascade of melanization promoted viral replication of HvAV-3h [35]. In addition to our results presented above, a variety of evidence suggests that virions produced in circulating viral vesicles are shed into the haemolymph [10,13,15], where they can also be acquired on the ovipositor of female wasps. Phylogenetic analysis indicates that ascoviruses evolved iridoviruses [36].…”
Section: Rna-sequencing Data Validationsupporting
confidence: 76%
“…for TnAV, and 14 days p.i. for SfAV [13]. This study and others [15,16] demonstrated that ascoviruses have a unique reproduction strategy that distinguishes them from all other viruses and most intracellular pathogens.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations